A Perancangan UI/UX Sistem Informasi PPDB Berbasis Website Pada SD IT Mufidatul Ilmi : sistem informasi, UI/UX, design thinking - Afrianti, Nurhafizah; Komalasari, Dinny (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
The increasingly rapid development of information and communication technology has changed the way people interact with the world. This also applies to the process of accepting new students (PPDB), which is currently mostly done online. SD IT Mufidatul Ilmi is a private school that has quite a large number of interested people. The current PPDB system still has several shortcomings, such as an unattractive display and navigation that is not user-friendly. This can cause difficulties for prospective students and parents in registering. Therefore, it is necessary to design a PPDB system UI/UX that can overcome these shortcomings. With good UI/UX design, the PPDB system can become more attractive, easier to use, and can provide a positive experience for users. This research uses the design thinking method to design the UI/UX of the website-based PPDB information system at SD IT Mufidatul Ilmi. This method consists of five stages, namely: Empathy, Define, Ideate, Prototype, Testing. The research results show that designing the UI/UX of the website-based PPDB information system at SD IT Mufidatul Ilmi using the design thinking method can produce a system that is more attractive, easy to use, and can provide a positive experience for users.